The Impact of Students’ Personality Traits Toward Speaking Skills - Tri Astuti, Missi (English Lecturers and Teachers Association (ELTA), 2024)
This study aimed to examine the effect of personality traits, extroversion and introversion, on students' speaking skills. This study used a correlational method with a quantitative design with 64 sample students of semester four, English Education Program of Universitas Islam Riau. Utilizing the Eysenck Personality Questionnaire (EPQ), students were classified into extroverted and introverted groups, and their speaking skills were evaluated based on pronunciation, grammar, vocabulary, fluency, and understanding. The results indicated that 71.88% of students were extroverted and 28.12% were introverted. Introverted students got a higher average speaking score (56.67) compared to extroverted students (51.41), statistical analysis showed that neither personality trait significantly affected speaking skills. The distribution of speaking skills affected personality traits for only 1% of extroverted and 0.9% of introverted, with both results statistically insignificant. The study concluded that educational strategies should not focus solely on personality traits but consider other factors such as motivation, learning strategies, and instructional quality. Keywords: Personality Traits; Speaking Skills